Correlation of creative thinking skill with STEAM readiness of biology pre-service teacher - Aidil Adhani; Fadhlan Muchlas Abrori; Linta Annisa (STKIP Persada Khatulistiwa Sintang, 2022)
Creative thinking skills are one of the 21st century skills that must be possessed by biology pre-service teachers. Someone with good creative thinking skills can more easily convey ideas, solve problems, and always think differently than usual. The aim of this study is to know how the relationship between creative thinking skills to STEAM rediness. This research is correlational quantitative research. The sampling technique used in this research is the quota sampling technique. The number of students used as a sample is 90 people with each batch consist of 30 samples. The instrument used in this study is a questionnaire, both to measure creative thinking skills and STEAM readiness. Data analysis techniques using Spearman rank correlation. The data shows the strong correlation between creative thinking skill and STEAM readiness with correlation coefficient value 0,622. The aspects of creative thinking skill are potential to make pre-service teacher more prepared to STEAM implementation at school. The better the creative thinking skills of biology pre-service teacher, the more prepared they will be in implementing STEAM later.